Diversity of Tartary Buckwheat (Fagopyrum tataricum) landraces from Liangshan, Southwest China: Evidence from morphology and SSR markers - Song, Yingjie; Cheng, Zhuo; Dong, Yumei; Liu, Dongmei; Bai, Keyu; Jarvis, Devra I.; Feng, Jinchao; Long, Chunlin (MDPI, 2022)
Tartary buckwheat (Fagopyrum tataricum) has been cultivated for over one thousand years in the Liangshan Prefecture of Sichuan, China. Growing population pressures, economic modernization pressures, and the erosion of traditional culture have led to the rapid loss of area covered by Tartary buckwheat landraces. Morphological and molecular characterization of 112 Tartary buckwheat accessions from 29 populations were assessed based on 10 morphological traits of seeds and 10 SSR markers, respectively. The coefficient of variation and Shannon index showed diversity within the morphological characteristics of the seeds. All accessions were divided into three categories according to phylogenetic dendrogram analysis, which was consistent with folk nomenclature and taxonomy. Genetic analysis using SSR markers identified 45 alleles with a mean value of 4.5 alleles per locus. The high average PIC value (0.459) indicated polymorphism of the SSR markers. The genetic similarity coefficient of the 112 Tartary buckwheat accessions showed a high level of genetic diversity ranging from 0.130 to 0.978. The genetic structure analysis revealed high genetic differentiation (Nei = 0.255). The folk nomenclature, folk taxonomy, and sociocultural norms may also contribute to a significant influence on the diversity of folk nomenclature and taxonomy. The assessment of the genetic diversity of Tartary buckwheat landraces and detection of SSR loci associated with traits could be used as scientific guidance for selecting Tartary buckwheat seed for improved production relative to local farmers and consumer preferences. Local traditional knowledge (seed exchange network) and culture also contribute to breeding and the maintenance of the genetic diversity of Tartary buckwheat.